COMMITTEES UNDER THE BOARD OF DIRECTORS OF JOINT STOCK COMPANY AS A TOOL OF CORPORATE MANAGEMENT AND FINANCIAL CONTROL - A. Yakovlev (Вестник университета)
The use of committees under the boards of directors as a tool for corporate management has investigated. The practice of forming committees under the boards of directors (supervisory boards) is expanding in Russia. This tool is used both in the pract ice of corporate management and corporate control. There are quite significant differences in the companies regarding the number and focus of committees. The audit, strategy, personnel and remuneration committees are the most common, more rarely - investment committees and budget.